(3ecGJHI ef CHj GdTjN GdeYGdis - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3hUdJ ecGJHI GdTjN GdWGgQ GdRci Pi GdfaS GdSGcfI hGdYbd GdRGgQ GdCHi hhbaJ Ydi eVehf aUhdgG s
(3BNQgG (B:s
(3hGdTGchf GdPjf BjShG ef QLYJg hdbGFg hbjGeg HSja GdMb JeJ HMeO hdi GdfYeI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B102s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GdJhMjO hGdedd hGdfMds